Enhancing Students’ Reading Skills Through Self-Directed Learning Strategy in Academic Reading Course - Dewi, Anggun Citra Sari; Hati, Gita Mutiara; Marpaung, Tiara Azzahra; Sasmita, Ruwaiza (UNIB Press, 2025)
One of the basic skills in a foreign language is the ability to read. The purpose of reading is to understand, analyze and explore the contents of the reading material they read. By reading we can more quickly master a foreign language. Academic reading courses are offered in the English Language Education study program as a provision for students to be able to understand academic texts which will be very useful later to enrich their knowledge and will also help them when writing scientific papers such as articles and theses. To be able to study online or outside of main lecture hours, students must have control over their learning process and be responsible for what and how they learn the foreign language (Merriam & Bierema, 2013). This learning strategy is known as Self-Directed learning. Learning with Self-Directed learning can increase students' knowledge, abilities and achievements in learning in the way they choose. This strategy is a mental process that is followed and supported by identifying and searching for information (Suknaisith, 2014).